Musik Seruling Bambu pada Kelompok Saiyo Sakato Desa Tebat Ijuk Kecamatan Depati VII “Deskripsi Musikologis” - Sepira, Qorie; Wimbrayardi Wimbrayardi; Ayuthia Mayang Sari (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This study aims to examine the relationship between text and melody in Bamboo Flute Music in Depati VII District. This research is qualitative with a descriptive content analysis approach. The research object is Bamboo Flute Music, with data collected through literature study, observation, interviews, and documentation. The research analyzed the data by examining the form, melody, and the relationship between text and melody in the song "Bungo di Laman". The results show that there are 10 kinds of rhythmic forms in this song, both of which are the development of previous forms and new formations. The flute melody in the tale "Bungo di Laman" is dominated by ascending melodic movement, where the melody tends to rise to a higher pitch. The descending movement in the flute melody is only used as a bridge to the next ascending movement. The same applies to the vocal melody in the tale, where the ascending movement is dominant and the descending movement only serves as a bridge. The pronunciation style of the story "Bungo di Laman" is predominantly syllabic, with 316 syllables pronounced syllabically.